1978
DOI: 10.1007/bf01981399
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine synthesis and its dependence on nervous activity

Abstract: The findings discussed in this paper mainly derived from studies on salivary glands, serving as model organs, indicate that the capacity to form the neurotransmitter acetylcholine, as judged by the activity of choline acetyltransferase, is influenced by the traffic of nerve impulses, as a long term effect. In the glands, choline acetyltransferase seems to be exclusively localized to the cholinergic nerves. In the postganglionic parasympathetic nerves of the glands, the activity of choline acetyltransferase dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
9
0

Year Published

1979
1979
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 76 publications
4
9
0
Order By: Relevance
“…Such a possibility has also been considered by the radiochemical assay of choline acetyltransferase in the heart (White & Wu 1973) and placenta (Welsch 1977). Using the control incubations described above, the choline acetyltransferase activity was found to be very low in denervated parotid glands, a finding which agrees with previous observations (see Ekstrom 1978). The remaining enzyme activity, about 1 % of that of the contralateral gland, can be accounted for, since some nerves persist in the gland after the denervation procedure ( A h & Ekstrom 1976).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Such a possibility has also been considered by the radiochemical assay of choline acetyltransferase in the heart (White & Wu 1973) and placenta (Welsch 1977). Using the control incubations described above, the choline acetyltransferase activity was found to be very low in denervated parotid glands, a finding which agrees with previous observations (see Ekstrom 1978). The remaining enzyme activity, about 1 % of that of the contralateral gland, can be accounted for, since some nerves persist in the gland after the denervation procedure ( A h & Ekstrom 1976).…”
Section: Discussionsupporting
confidence: 84%
“…In a previous study (Ekstrom 1975) where the ducts of several major salivary glands were tied in an animal, the intact gland(s) gained in weight and showed increased choline acetyltransferase activity compared with control glands in unoperated animals; this was thought to reflect increased traffic of secretory impulses in the nervous pathways to the gland (see Ekstrom 1978). In a previous study (Ekstrom 1975) where the ducts of several major salivary glands were tied in an animal, the intact gland(s) gained in weight and showed increased choline acetyltransferase activity compared with control glands in unoperated animals; this was thought to reflect increased traffic of secretory impulses in the nervous pathways to the gland (see Ekstrom 1978).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ekstrom (1978) suggested that changes of CHAT activity were produced by con¬ comitant alterations in cholinergic nerve activity. In view of this we explored the sodium-dependent, HC-3-inhibitable, high-affinity choline uptake.…”
Section: Discussionmentioning
confidence: 97%